Analisis Karakteristik Pekerja Miskin: Studi Kasus Di Kabupaten Lebong Tahun 2020 - Fedi, Siti Zuliana (Universitas Islam Negeri Alauddin Makassar, 2022)
Poverty is still a problem that afflicts all regions in Indonesia. In 2020 Bengkulu Province became the poorest province on the island of Sumatra with a poverty rate of 15.03 percent. The district/city poverty rate in Bengkulu Province is quite high, which is still in double digits. One of them is Lebong Regency, which based on BPS data in March 2020 has a poverty rate of 11.85 percent. But on the other hand, the open unemployment rate (TPT) in Lebong Regency is relatively low at 3.93 percent in 2020. The high poverty rate coupled with the low unemployment rate indicates the phenomenon of working poor in the Lebong Regency. This study aims to determine the characteristics that characterize the working poor in Lebong Regency. The analytical method used is the descriptive analysis method using tables and the inferential analysis method using binary logistic regression. The results showed that the characteristics of the working poor in the Lebong Regency were workers who were young and prime/middle and had low education, namely high school and below. Keywords: charahteristics, working poor, binary logistic regression.